CISSP exam cram - Gregg, Michael (Pearson IT Certification, 2017)
This is the eBook version of the print title. Note that the eBook does not provide access to the practice test software that accompanies the print book. Access to the digital edition of the Cram Sheet is available through product registration at Pearson IT Certification; or see instructions in back pages of your eBook. CISSP Exam Cram, Fourth Edition, is the perfect study guide to help you pass the tough new electronic version of the CISSP exam. It provides coverage and practice questions for every exam topic, including substantial new coverage of encryption, cloud security, information lifecycles, security management/governance, and more. The book contains an extensive set of preparation tools, such as quizzes, Exam Alerts, and two practice exams. Covers the critical information you'll need to pass the CISSP exam! Enforce effective physical security throughout your organization Apply reliable authentication, authorization, and accountability Design security architectures that can be verified, certified, and accredited Understand the newest attacks and countermeasures Use encryption to safeguard data, systems, and networks Systematically plan and test business continuity/disaster recovery programs Protect today's cloud, web, and database applications Address global compliance issues, from privacy to computer forensics Develop software that is secure throughout its entire lifecycle Implement effective security governance and risk management Use best-practice policies, procedures, guidelines, and controls Ensure strong operational controls, from background checks to security audits.
Online resource; title from PDF title page (EBSCO, viewed November 9, 2017)
Keywords: Computer security -- Study guides -- Examinations; Sécurité informatique; Examens; Guides de l'étudiant; COMPUTERS / Certification Guides / General; COMPUTERS / Security / General; Computer security; Examinations; Study guides